The early textual transmission of John: stability and fluidity in its second and third century Greek manuscripts - Bell, Lonnie (New testament tools, studies and documents, 2018)
Intro -- ‎Contents -- ‎Acknowledgments -- ‎Abbreviations -- ‎Chapter 1. Introduction -- ‎1. Introduction to the Study -- ‎2. Major Approaches to the Early Papyri -- ‎3. My Question and Approach -- ‎4. Rethinking Some "Free" Texts -- ‎5. Structure of the Study -- ‎Chapter 2. Fragments without Full Overlap in P66 or P75 -- ‎1. P52 (P.Ryl. III 457) -- ‎2. P90 (P.Oxy. L 3523) -- ‎3. P107 (P.Oxy. LXV 4446) -- ‎4. P108 (P.Oxy. LXV 4447) -- ‎5. P109 (P.Oxy. LXV 4448) -- ‎6. P121 (P.Oxy. LXXI 4805) -- ‎7. P5 (P.Oxy. II 208 & XV 1781) -- ‎8. P22 (P.Oxy. X 1228) -- ‎9. P28 (P.Oxy. XIII 1596) -- ‎Chapter 3. Fragments with Full Overlap in P66 Only -- ‎1. P95 (P.Laur. inv. II/31) -- ‎2. P39 (P.Oxy. XV 1780) -- ‎Chapter 4. Fragments with Full Overlap in P66 and P75 -- ‎1. P106 (P.Oxy. LXV 4445) -- ‎2. P119 (P.Oxy. LXXI 4803) -- ‎3. 0162 (P.Oxy. VI 847) -- ‎Chapter 5. Results and Implications -- ‎P5 -- ‎P106 -- ‎P90 -- ‎P28 -- ‎P95 -- ‎P52 -- ‎P107 -- ‎P121 -- ‎P119 -- ‎0162 -- ‎P108 (none) -- ‎P109 (none) -- ‎P22 (none) -- ‎P39 (none) -- ‎P28 -- ‎P95 -- ‎P95 -- ‎P107 -- ‎P90 -- ‎P119 -- ‎P108 -- ‎P28 -- ‎0162 -- ‎P5 -- ‎P109 -- ‎P106 -- ‎P22 -- ‎P39 (none) -- ‎P52 (none) -- ‎P121 (none) -- ‎Works Cited -- ‎Index of Authors -- ‎Index of Subjects -- ‎Index of Manuscripts -- ‎New Testament Manuscripts -- ‎Other Manuscripts -- ‎Index of Biblical Passages -- ‎Old Testament/Septuagint -- ‎New Testament.